Technology of determining the rational structure of the information and telecommunication system of the state border guard service of ukraine on the basis of reserve channels - Басараб, Олександр Корнійович (Ukrainian Information Security Research Journal, 2013)
The effectiveness of the border protection depends on die efficiency of die telecommunications system of die State Border Guard Service of Ukraine. The availability of its individual segments do not meet international requirements for telecommunication systems. Existing methods of increasing of die efficiency of telecommunication systems do not include features of telecommunication system of die State Border Guard Service of Ukraine, namely the impact of its functioning on the effectiveness of die border. The article presents die technology for determining the rational structure of die information and telecommunication system of die State Border Guard Service of Ukraine on the basis of reserve channels taking into consideration die indicator of the operational and service activiti of the border guard units. This technology allows to make the rational choice of building a network component of information and telecommunication system of the State Border Guard Service of Ukraine with die reservation of channels and using the dynamic routing protocol.